Proposed Third Amendment of the Articles of Agreement. (International Monetary Fund, 2004)
This chapter provide details of the proposed Third Amendment of the Articles of Agreement of the IMF. This paper also examines the conditions for the imposition of suspension of voting and related rights of a member, then the consequences of suspension, and finally the conditions and effects of a termination of suspension. The Fund's Articles of Agreement empowers the Fund to declare a member ineligible to use the general resources of the Fund if the member fails to fulfil any of its obligations under the Articles. The commentary in the chapter analyzes the proposed amendment and describes the main aspects of the new power that would be conferred upon the Fund. The chapter also describes the procedure for the adoption of the proposed amendment. It proposes a resolution for adoption by the Board of Governors.